Complete remission of severe nephrotic syndrome: a case report of outpatient therapy - Putra, Kadek Nova Adi (International Journal of Advances in Medicine, 2025)
Nephrotic syndrome is characterized by massive proteinuria, hypoalbuminemia, generalized edema, and hyperlipidemia, often resulting from primary glomerular diseases or secondary systemic conditions. Severe hypoalbuminemia and dyslipidemia can lead to life-threatening complications, necessitating timely and effective treatment. Here, this report presents a case of a 21-year-old male presenting with generalized edema, severe hypoalbuminemia (0.6 g/dl), and marked hyperlipidemia (LDL 501 mg/dl, triglycerides 401 mg/dl), consistent with nephrotic syndrome. Despite the recommendation for hospitalization, the patient opted for outpatient care. Management included high-dose oral corticosteroids, angiotensin-converting enzyme (ACE) inhibitors, dual lipid-lowering therapy (statin and fibrate), diuretics, nutritional support, and close biochemical monitoring. Over 24 weeks, the patient demonstrated complete clinical and laboratory remission. Proteinuria resolved by week 8, serum albumin normalized by week 16, and lipid profile returned to baseline by week 24. No significant complications were observed during follow-up. This case highlights the potential for successful outpatient management of severe nephrotic syndrome in a compliant and closely monitored patient. It underscores the importance of individualized care, adherence, and interdisciplinary collaboration in achieving favorable outcomes outside a hospital setting.